2015
DOI: 10.1212/wnl.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

Association of hospitalization with long-term cognitive and brain MRI changes in the ARIC cohort

Abstract: Objective: To determine whether hospitalization is associated with subsequent cognitive decline or changes on brain MRI in a community-based cohort.Methods: Baseline and follow-up cognitive testing (n 5 2,386) and MRI scans with standardized assessments (n 5 885) were available from a subset of white and black participants in the Atherosclerosis Risk in Communities study. Cognitive tests included the Delayed Word Recall Test (DWRT), Digit Symbol Substitution Test (DSST), and Word Fluency Test (WFT). Hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…We were not able to explore this mechanism, because only 5% of the cohort had ICD‐9 codes indicating delirium, reflecting underreporting of delirium in claims records . Another study examined the association of hospitalization with long‐term cognitive decline and brain magnetic resonance imaging (MRI) changes; they found hospitalization was associated with higher odds of increasing ventricular size, and there was modest evidence of mediation of the association of hospitalization and cognitive decline when ventricular change was added to the model (there was little evidence of mediation by white matter hyperintensities) . Finally, a recent MRI study demonstrated a relationship between more frequent hospitalizations and smaller brain volumes and lower white matter integrity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were not able to explore this mechanism, because only 5% of the cohort had ICD‐9 codes indicating delirium, reflecting underreporting of delirium in claims records . Another study examined the association of hospitalization with long‐term cognitive decline and brain magnetic resonance imaging (MRI) changes; they found hospitalization was associated with higher odds of increasing ventricular size, and there was modest evidence of mediation of the association of hospitalization and cognitive decline when ventricular change was added to the model (there was little evidence of mediation by white matter hyperintensities) . Finally, a recent MRI study demonstrated a relationship between more frequent hospitalizations and smaller brain volumes and lower white matter integrity .…”
Section: Discussionmentioning
confidence: 99%
“…H ospitalization of older persons is associated with subsequent increases in rate of cognitive decline [1][2][3][4][5] and risk of dementia. 6 The association increases with advancing age, 7,8 but its basis is uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These prevalence and incidence rates suggest that delirium affects millions of hospitalized elderly adults every year . Although delirium is an acute condition, it has lasting effects, with fully one‐third of patients on medicine units experiencing persistent symptoms after having had delirium . Individuals undergoing surgery have been shown to have a reduction in physical function for more than 30 days and cognitive impairment for up to a year because of the effects of delirium .…”
mentioning
confidence: 99%
“…2 Although delirium is an acute condition, it has lasting effects, with fully one-third of patients on medicine units experiencing persistent symptoms after having had delirium. 3 Individuals undergoing surgery have been shown to have a reduction in physical function for more than 30 days and cognitive impairment for up to a year because of the effects of delirium. 1 Individuals with delirium also have higher rates of subsequent dementia, institutionalization, mortality, and healthcare costs after discharge than those without.…”
mentioning
confidence: 99%